Financial Management Practices of School Heads in Non-Fiscally Autonomous Secondary Schools in Sorsogon, Philippines - Donna F. Espela; Gerry S. Digo; Chris John P. Dayson; Jonnell G. Borabo; Cristine Mae E. Arevalo (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The study focuses on linking the Philippine standards on fiscal management in the education sector with the fiscal practices of the school heads of non-fiscally autonomous secondary schools. Specifically, this paper describes school heads' financial management, identifies the school heads' financial management practices, and proposes an integrated financial management model for public secondary school heads. Methodology: A qualitative research method through a case study design was used. School heads from non-fiscally autonomous secondary schools in the province of Sorsogon. The data were gathered through an interview with the participants and were analyzed using thematic analysis. Main Findings: Schools rely on MOOE and SEF but seek additional funds due to budget limitations. School heads prioritize student outcomes and facility improvements. Procurement follows the Government Procurement Reform Act, emphasizing transparency. Disbursement and liquidation are systematic and timely. Best practices include stakeholder engagement, audits, and alignment with SIP and AIP. A developed financial management model for school heads emphasizes efficiency, integrity, transparency, and accountability. Novelty/Originality of this study: This research identifies key financial management practices of school heads, including fund diversification, prioritized allocation, adherence to legal bases, and stakeholder engagement. A novel financial management model is developed, incorporating efficiency, integrity, transparency, and accountability.